FILM FESTIVAL POLITICS AND SPECTATORSHIP (NETWORK AFFECTS) - VIRGINÁS, Péter (Studia Universitatis Babeș-Bolyai Philosophia, 2016)
Film Festival Politics and Spectatorship (Network Affects). The article is highly relevant for the relatively recent field of film festival research, and has a more limited relevance for the fields of film theory and philosophy of film. The originality of the article is that it aims to infuse the field of film festival research with insights regarding the collective experiential-emotional aspects of festival-events, inspired mainly by contemporary affective science and network-theory.